Analisis Kebijakan Keselamatan Pasien di Instalasi Rawat Inap Rumah Sakit Umum Daerah Arifin Achmad Provinsi Riau: Kebijakan Keselamatan Pasien - fristasya, andra; Handoko, Bobi; Firdaus, Muhammad; Mutiara, Sherly (Jurnal Administrasi Publik dan Bisnis, 2024)
This study aims to find out about Patient Safety Policy Analysis at the inpatient insrallation at the Arifin Achmad Regional General Hospital, Riau Province. This type of research in qualitative with an analytic descriptive approach. This research was conducted on 9 February - 30 June 2023 at Arifin Achmad Hospital, Riau Province. There are 5 informants in this study and this research uses the Content Analysis model.